Effect of internal stress on cyclic fatigue failure in .06 taper ProFile - Hye-Rim Jung; Jin-Woo Kim; Kyung-Mo Cho; Se-Hee Park (Korean Academy of Conservative Dentistry, 2012)
Objectives The purpose of this study was to evaluate the relation between intentionally induced internal stress and cyclic fatigue failure of .06 taper ProFile. Materials and Methods Length 25 mm, .06 taper ProFile (Dentsply Maillefer), and size 20, 25, 30, 35 and 40 were used in this study. To give the internal stress, the rotary NiTi files were put into the .02 taper, Endo-Training-Bloc (Dentsply Maillefer) until auto-stop by torque controlled motor. Rotary NiTi files were grouped by the number of induced internal stress and randomly distributed among one control group and three experimental groups (n = 10, Stress 0 [control], Stress 1, Stress 2 and Stress 3). For cyclic fatigue measurement, time for separation of the rotary NiTi files was recorded. The fractured surfaces were observed by field emission scanning electron microscope (FE-SEM, SU-70, Hitachi). The time for separation was statistically analyzed using two-way ANOVA and post-hoc Scheffe test at 95% level. Results In .06 taper ProFile size 20, 25, 30, 35 and 40, there were statistically significant difference on time for separation between control group and the other groups (p < 0.05). Conclusion In the limitation of this study, cyclic fatigue failure of .06 taper ProFile is influenced by internal stress accumulated in the files.